GORAB scaffolds COPI at the trans-Golgi for efficient enzyme recycling and correct protein glycosylation - Tomasz M. Witkos (Nature Portfolio, 2019)
COPI is recruited to the membrane by binding to Arf GTPases. Here the authors find that GORAB, a trans-Golgi protein, promotes COPI recruitment by forming membrane domains that also contain the COPI-interacting protein Scyl1, which is required for efficient glycosylation of cargo proteins.